Liberia - 2008 Public Expenditure Management and Financial Accountability Review - World Bank (World Bank, 2012)
The 2008 Public Expenditure Management and Financial Accountability Review (PEMFAR) assess Liberia's public expenditure performance along four main dimensions: macroeconomic, institutional, allocations between sectors, and allocations within key sectors. At the macroeconomic level, it describes the external economic constraints and opportunities that will drive growth and revenue mobilization over the medium term and determine the likely fiscal envelope (chapter one). It next reviews the institutional structures that guide and ensure appropriate resource allocation and assesses the strength and weaknesses of the current systems using a standardized public expenditure and financial accountability scoring system (chapter two). It then assesses how public expenditure has been allocated between sectors and priorities (chapter three). It lastly reviews the allocation of resources within two priority sectors, health and education (chapter four).